Penggunaan Celebrity Endorser pada Media Sosial Instagram dalam Meningkatkan Brand Engagement - Emilia Abby; Irwansyah Irwansyah (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research by using the concept of social media instagram and brand engagement, discusses how the process of forming brand engagement using the celebrity endorser on Instagram. Through the desk research method and getting data from secondary data from previous studies, it can be seen that by using celebrity endorser on Instagram social media, it can increase brand engagement that the brand gets from followers of selected celebrity Instagram accounts. Because currently Instagram is the most popular social media for uploading photos and interacting in each upload, the use of celebrity endorsers can increase brand engagement from the stage of dating, casual, active, committed to the stages of loyalists